The influence of corporate culture on organizational commitment : case study of semiconductor organizations in Malaysia - Ooi, Keng Boon; Arumugam, Veeri (Sunway University College, 2006)
The purpose of this study was to investigate the influence of four dimensions of corporate culture (teamwork, communication, reward and recognition, and training and development) on employees? organizational commitment within six major Malaysian semiconductor packaging organizations. Despite extensive research on corporate culture, very little empirical research has examined this area of study. Hierarchical regression analyses were employed to test the research hypotheses. The results of this study revealed that communication, training and development, reward and recognition, and teamwork are positively associated with employees? commitment. Also, communication was perceived as a dominant corporate culture dimension; it was associated with significant improvements in employees? organizational commitment. This study contributes to a better understanding of the influence of corporate culture on organizational commitment among employees within the context of the Malaysian semiconductor sector. Suggestions for future research are discussed.